Faktor–faktor yang mempengaruhi konsumen dalam menggunakan dan berhutang dengan kartu kredit di Jabodetabek - Nesia Ardelia; Farah Margaretha Leon (Jurnal Akuntansi, Keuangan, dan Manajemen, 2021)
Purpose: This study discussed the factors that influence the use and debt of credit cardholders in Jakarta and surrounding areas (Jakarta, Bogor, Depok, Tangerang, Bekasi) Research methodology: The dependent variable used in this study is the use of credit cards and debts on credit cards. This study's independent variables were demographic factors, credit card feature factors, and attitude towards money factors. The sample of this study was 333 respondents using the purposive sampling technique. The data analysis model used is Ordinary Least Square (OLS). Results: The results showed that there were influences from demographic factors (age, income, family size), features on credit cards (credit limits), and attitudes towards money (the main payment method with credit cards, card tenure) on the use of credit cards; also, demographic factors (gender, type of work, level of education, income) and attitude towards money (minimum payment) on credit card debt. Therefore the factors that banks need to consider to increase their income, and the government for control of public expenditure, also the public to pay more attention to spending on their credit cards so that there is no accumulation of debt that cannot be paid. Limitations: This study has several limitations of specifically only examines the people who are in Jakarta and their surroundings (Jabodetabek) and examines demographic factors, features on credit cards, and attitudes. Contribution: This study will examine demographic factors, features on cards, and attitudes towards money by uniting variables per category into a unified category. The indicators in this study are adjusted to the community in Indonesia. Keywords: Attitude towards money, Credit cards, Credit card features, Demographics